Peran Regulasi Dan Kebijakan Publik Dalam Penguatan Tata Kelola Zakat Nasional - Warto, Warto; Atep Hendang Waluya; Firman Setiawan (Institut Agama Islam Negeri Ponorogo, 2025)
Zakat plays a strategic role in supporting socio-economic development and equitable welfare distribution in Indonesia. However, the optimization of national zakat potential still faces a significant gap between estimated potential and actual collection. This article aims to analyze the role of regulation and public policy in strengthening national zakat governance by highlighting regulatory dynamics, institutional effectiveness, and the synergy between the government, the National Amil Zakat Agency (BAZNAS), and Zakat Management Organizations (LAZ). The study employs a qualitative approach with descriptive-analytical methods through literature review, secondary data, and policy comparisons based on academic works and institutional reports. The findings indicate that zakat regulation, particularly after the enactment of Law No. 23 of 2011, provides a stronger legal foundation for zakat institutions but still encounters challenges in harmonizing technical regulations, fostering multisectoral coordination, and implementing modern governance standards based on digitalization. The analysis also reveals that public policies adaptive to socio-economic and technological developments play a significant role in enhancing transparency, accountability, and public trust. The article concludes by emphasizing the importance of reformulating zakat policies to be more integrative with the national development agenda, particularly the Sustainable Development Goals (SDGs), as well as strengthening regulatory systems capable of driving zakat realization closer to its national potential.